HUBUNGAN KECEPATAN LARI 40 METER DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS V SDN 008 PANGKALAN KERINCI - Lismi Susanti; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of male student in class V SDN 008 Pangkalan Kerinci while do long jump, research found while student do run start was not optimal. The purpose of this research is to see the correlation of 40 yard running speed with long jump result with squat style of student in class V SDN 008 Pangkalan Kerinci Primary School. Population in this research were all male students in class V SDN 008 Pangkalan Kerinci Primary School amount 37 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 37 people. Research instrument used 40 yard speed running test and long jump test with squat style. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is correlations of 40 yard running speed with the long jumpresult with squat style of student inclass V SDN008 Pangkalan Kerinci Primary School.Key word : 40 yard running speed, long jump.